Understanding Identity and Diaspora: The Case of the Sama-Bajau of Maritime Southeast Asia - Matthew Constancio Maglana (Department of History, Faculty of Humanities, Diponegoro University, 2016)
The Sama-Bajau or the Sinama-speaking peoples are deemed to be the most widely dispersed indigenous ethno-linguistic group in maritime Southeast Asia. The Sama-Bajau “diaspora,” which constitute a locus of points across territorially-defined spaces, gives rise to specific socio-cultural contexts which in turn results in the emergence of distinct notions of identity. This diaspora, therefore, gives the student of culture the opportunity to observe ethno-genesis as either “completed,” incipient or on-going processes of the creation of identities that exhibit rare tensions between ideas of sameness and difference. The former is a function of a common origin, which may be real or perceived, while the latter results from site-specific sources of distinction such as those brought about by socio-cultural adaptation to environment, intercultural contact with other peoples or other external sources of culture change. This article interrogates this tension between sameness and difference through a selection of examples seen in labels of self-designation, language, and, religious and ritual practices.